2018
DOI: 10.15835/nbha46110983
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Drought Tolerance in Trifoliate Orange by Mycorrhiza: Changes in Root Sucrose and Proline Metabolisms

Abstract: Sucrose and proline metabolisms are often associated with drought tolerance of plants. This study was conducted to investigate the effects of two arbuscular mycorrhizal fungi (AMF) species (Funneliformis mosseae and Paraglomus occultum) on root biomass, lateral root number, root sucrose and proline metabolisms in trifoliate orange (Poncirus trifoliata) seedlings under well-watered (WW) or drought stress (DS). All the AMF treatments significantly increased root dry weight, taproot length, and the number of late… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(15 citation statements)
references
References 36 publications
1
11
0
Order By: Relevance
“…Among the three nutrient uptakes analyzed, the mycorrhizal contributions to the uptake of P were higher than the uptake of N and K. AMF-inoculated plants were proved for escalated plant growth by an increase in N, P, and K uptake during drought stress [ 38 , 48 , 49 , 50 ]. Nitrogen and phosphorous are the principal nutrients of plant cells that render the cell characters by altering cell structure and functions for growth patterns [ 42 , 48 , 51 ]. AMF colonization enhanced P concentration under all treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Among the three nutrient uptakes analyzed, the mycorrhizal contributions to the uptake of P were higher than the uptake of N and K. AMF-inoculated plants were proved for escalated plant growth by an increase in N, P, and K uptake during drought stress [ 38 , 48 , 49 , 50 ]. Nitrogen and phosphorous are the principal nutrients of plant cells that render the cell characters by altering cell structure and functions for growth patterns [ 42 , 48 , 51 ]. AMF colonization enhanced P concentration under all treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have explained that AMF have the ability to absorb and transfer N to the nearby plants or host plants (Hodge and Storer, 2015; Battini et al, 2017; Turrini et al, 2018). Zhang et al (2018a) have demonstrated AMF mediated increased allocation of shoot biomass to panicles and grains through increased N and P redistribution to panicles particularly under low fertilizer levels. Translocation of N into seeds is enhanced from heading to maturity.…”
Section: Amf and Mineral Nutritionmentioning
confidence: 99%
“…AM have shown significant roles in the uptake of soil nutrients, especially of N and P, which can effectively promote the growth of host plants [6]. AM also increase allocation of shoot biomass through increased N and P redistribution to panicles, particularly under low fertilizer levels [24]. In this experiment, the seedlings receiving higher fertilizer doses resulted in higher nutrient accumulation.…”
Section: Nutrient Accumulationmentioning
confidence: 69%